Bathed in prayer [large type] - Karon, Jan, 1937- (Thorndike Press large print basic series., 2018)
A collection of prayers, sermons, and inspirational passages that incorporates material from each of the novels in the Mitford series. In addition, fans will get to hear directly from author Jan Karon, in a brand-new essay about her own personal journey in faith and the ways that the Mitford novels have impacted her.